Pengembangan Barbinto (Baruasa Binto’ Toeng) Sebagai Cemilan Sehat Bagi Anak Sekolah Dasar - Kurniati, Yessy; Hadza, Roza Qoni; Alam, Syamsul; Damayaty, Dwi Santy; Muzakkir, Muzakkir (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2025)
Snacks for school-age children are important for meeting daily nutritional needs, but both excess and deficiency of nutrients can affect children's growth and development. This study aims to develop a healthy snack based on Binto' Toeng flour (Barbinto) and to test its acceptability and nutritional content. The research was conducted using an experimental design with a Randomized Complete Block Design (RCBD) from April to June 2024, involving the preparation of gude bean flour, the production of Barbinto, organoleptic testing, and nutritional analysis. The organoleptic test showed that the control formulation had the highest preference score from both trained panelists and consumer panelists, with mean values of 5.23 and 5.80, respectively. Among the three experimental formulations, the one with 10% gude bean flour had the highest mean score of 5.2 and 5.05. Nutritional analysis indicated an increase in protein, fiber, ash, Vitamin A, and iron content, although there were decreases in carbohydrate, fat, water, Vitamin C, and zinc levels. Barbinto is expected to become a healthy snack option for schoolchildren, but innovations are needed to reduce the off-flavor in the product.